Fronto Linija: kurioje puseje liksi . Front Line: Which Side Will you Be On? - Juzenas, Audrius (Lithuania, 1999)
Soros Documentary Fund The film exposes children’s rights violations in Lithuania by documenting acute poverty, drug abuse and violence among the children, within their families and on the streets.